2017
DOI: 10.1590/s1806-92902017000900005
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional value of Brazilian distillers dried grains with solubles for pigs as determined by different methods

Abstract: -The objective of this study was to determine the digestibility coefficient (DC) of nutrients and the digestible energy (DE), and metabolizable energy (ME) values of distillers dried grains with solubles (DDGS) produced in Brazil by different methods. Eight barrows with 23.3±4.1 kg were housed in metabolic cages in a randomized block design and fed diets containing 0, 200, 400, and 600 g kg -1 of corn DDGS. We determined the digestibility of dry matter (DM), organic matter (OM), crude protein (CP), ether extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 27 publications
3
7
1
3
Order By: Relevance
“…However, regardless of the source, it was observed that DDGS inclusion in the diets resulted in an increase in NDF content and worsening in diet DC compared with the diet with corn and soybean meal. The present results are similar to a study that evaluated inclusions of 200, 400, and 600 g kg −1 of corn DDGS and reported a decline in the DC of NDF as the DDGS inclusion increased (Corassa et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…However, regardless of the source, it was observed that DDGS inclusion in the diets resulted in an increase in NDF content and worsening in diet DC compared with the diet with corn and soybean meal. The present results are similar to a study that evaluated inclusions of 200, 400, and 600 g kg −1 of corn DDGS and reported a decline in the DC of NDF as the DDGS inclusion increased (Corassa et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…The reduction in DC (Table 7) and the digestible fraction (Table 8) of OM, DM, MM, NDF, and EE with increasing DDGS inclusion is probably related to the fiber fraction in the tested ingredients, in which this concentration is almost three times higher than that of the original grains (Pedersen et al, 2014). Quantities above 600 g kg −1 NDF were observed in the DDGS of the present study, contributing to differences in DDGS energy digestibility as also observed by Corassa et al (2017) and Anderson et al (2012).…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations